Theatre Semiotics : Text and Staging in Modern Theatre - Toro, Fernando de, 1950- (Book collections on Project MUSE., 1995)
Theatre Semiotics provides a thorough argument for the place and the necessity of semiotics within the interpretive process of theatre.